D‐OCT‐assisted and histology‐controlled evaluation of 1064 nm Nd:YAG laser therapy of basal cell carcinomas - Ariana Palacio; Karla Medrano; Jon Holmes; Erhard Bierhoff; Uwe Reinhold (Wiley, 2023)
Abstract Background Basal cell carcinomas (BCC) have classically been surgically removed. Alternative treatments for superficial BCC include local immunotherapy, topical chemotherapy and photodynamic therapy. Recent data suggest 1064 nm Nd:YAG laser as a new treatment for those lesions. Dynamic optical coherence tomography (D‐OCT) is an established imaging procedure analysing BCC margins and its vascular plexus. Objectives Our goal is to further evaluate 1064 nm Nd:YAG laser therapy of BCC as a potential alternative treatment, employing D‐OCT and histopathology to standardise effective treatment protocols. Methods In this retrospective cohort study, 50 histologically confirmed superficial and nodular BCC with tumour thickness ≤1 mm were treated with 1064 nm Nd:YAG laser. Initial D‐OCT scans were performed and repeated for 3 months posttreatment. Tumoral clearance was histologically confirmed and local adverse effects, patient tolerability and satisfaction were recorded. Clinical remission was evaluated after 1 year. Results Complete clearance was achieved in 78% of BCC (39/50) at a 3‐month follow‐up. Treatment failures were slightly more likely to correspond to superficial BCC (91%, 10/11) of thickness ≤0.5 mm (73%, 8/11), located on the trunk (64%, 7/11). No treated lesions presented scarring. Patient satisfaction and tolerability displayed excellent results. Remission at 1 year occurred in 100% of initially cleared BCC (35/35, four patients were lost to follow‐up due to nonmedical reasons). Conclusions OCT‐assisted 1064 nm Nd:YAG laser treatment of superficial BCC is a safe and effective method with excellent patient satisfaction, tolerability, practicability and cosmetic end result.